The Effect of Using the Sharing Application (Tik-Tok) on the Character Development of Elementary School Children - Fatmawati Nur Hasanah; Kristiyah Kristiyah (Program Studi PGMI STAI Daruttaqwa Gresik, 2023)
The development of information technology has changed people's lives in all civilizations and cultures. One of the various and most favorite social media for elementary school children today is the sharing application